The principle of the rationality in the literary configuration of love - Dionei Mathias (FronteiraZ, 2016)
Emotions and rationality play a central role in Elfriede Jelinek’s novel Die Ausgesperrten (Wonderful, Wonderful Times, English translation published in 1990), from 1980. For a long time, rationality was considered the most important in decisionmaking situations, interactions, behavior and ways of conceptualizing the body, whereas emotions were seen as a destabilizing element. In her novel, Elfriede Jelinek seems to show that the primacy of rationality continues to produce monsters. With four protagonists, she covers all social classes, creating characters that do not know their emotions, but that see in rationality a secure tool to solve all conflicts they are confronted with. Thus, body and behavior, desire and belonging, to mention some elements of the configuration of love, end up subdued by the principle of rationality, whereas emotions remain silenced.